2018
DOI: 10.1007/s12031-018-1081-7
|View full text |Cite
|
Sign up to set email alerts
|

Association of GABAA Receptor Gene with Epilepsy Syndromes

Abstract: GABA has always been an inviting target in the etiology and treatment of epilepsy. The GABRA1, GABRG2, and GABRD genes provide instructions for making α1, ϒ2, and δ subunits of GABAA receptor protein respectively. GABAA is considered as one of the most important proteins and has found to play an important role in many neurological disorders. We explored the association of GABAA receptor gene mutation/SNPs in JME and LGS patients in Indian population. A total of 100 epilepsy syndrome patients (50 JME and 50 LGS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…Crestin expression, however, is reduced, with hypo-methylation of both the neighboring CpG site and associated DMR. Gabra1 , a GABA receptor subunit (Bhat et al, 2018) has decreased expression while the associated DMR is hyper-methylated, demonstrating a relationship between methylation and gene expression. Riox1 and wdr5 , respectively, a histone demethylase and histone methyltransferase (Aravind et al, 2011; Tao et al, 2013), exhibit decreased expression while the endosomal GTPase rab11bb (Clark et al, 2011) has increased expression, but all three are surrounded by a mixture of hyper and hypo-methylated sites ( riox and wdr5 ) and DMRs ( rab11bb ).…”
Section: Resultsmentioning
confidence: 99%
“…Crestin expression, however, is reduced, with hypo-methylation of both the neighboring CpG site and associated DMR. Gabra1 , a GABA receptor subunit (Bhat et al, 2018) has decreased expression while the associated DMR is hyper-methylated, demonstrating a relationship between methylation and gene expression. Riox1 and wdr5 , respectively, a histone demethylase and histone methyltransferase (Aravind et al, 2011; Tao et al, 2013), exhibit decreased expression while the endosomal GTPase rab11bb (Clark et al, 2011) has increased expression, but all three are surrounded by a mixture of hyper and hypo-methylated sites ( riox and wdr5 ) and DMRs ( rab11bb ).…”
Section: Resultsmentioning
confidence: 99%
“…This lowers surface expression of mature protein [ 160 ], in turn reducing GABA evoked chloride currents, leading to neuronal disinhibition by preventing hyperpolarization of membrane [ 161 ]. Studies have shown that R220H variant of GABRD can be a susceptibility allele for JME [ 162 , 163 ]. In contrast, Lenzen et al found no association between the R220H variant and JME among 562 German patients and 664 controls [ 164 ].…”
Section: Genetic Studies Of Common Epilepsiesmentioning
confidence: 99%
“…The γ2 subunit was reported to change the kinetics of GABA A related to channels and to the synaptic and postsynaptic clustering and maintenance. 16 , 17 , 18 , 19 C588T, located in the GABRG2 gene encoding the γ2 subunit, has previously been shown to cause genetic generalized epilepsy (GGE) risk and response to AEDs 20 , 21 , 22 ; however, other results were found to have conflicting results. 23 , 24 , 25 , 26 …”
Section: Introductionmentioning
confidence: 99%
“…The γ2 subunit was reported to change the kinetics of GABA A related to channels and to the synaptic and postsynaptic clustering and maintenance. [16][17][18][19] C588T, located in the GABRG2 gene encoding the γ2 subunit, has previously been shown to cause genetic generalized epilepsy (GGE) risk and response to AEDs [20][21][22] ; however, other results were found to have conflicting results. [23][24][25][26] Here, we aimed to explore whether the GABRG2 C588T polymorphism predicts susceptibility to GGE and to evaluate the role of GABRG2 in epilepsy treatment.…”
Section: Introductionmentioning
confidence: 99%